Phenotypic and molecular investigation of biofilm formation of Enterobacter cloacae causing urinary tract infections - Jabal Kadhim , Furqan; K. A. Al-Hassani, Mithal ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
Urinary tract infections represent a major expensive, a global common public health issue owing to their high prevalence and the struggling associated with their management. The current investigation aimed to identify the phenotypic and molecular characteristics of biofilm formation of E. cloacae isolates from UTIs by investigated the rate of distribution for two important genes namely: csgA and csgD. The current investigation demonstrated that the studied isolates of E. cloacae isolated from UTIs had a biofilm production rate at 80%. The statistical analysis outcomes indicate significant differences at 0.01 probability level. The outcomes of PCR for (20) E. cloacae isolates showed that the prevalence rates of the three studied genes were 70% and 65% for: csgA and csgD, respectively. The results of statistical analysis indicated that numbers of positive isolates was significantly higher (p<0.05) than negative samples for studied genes (csgA and csgD). Conclusion: The results of the current study confirm the clinical challenge posed by biofilm-forming E. cloacae strains, which have the ability to evade host defenses and classical antimicrobial treatments. The ability of E. cloacae to form biofilms was enhanced by 80%, which reinforced its virulence and survival, particularly in hospital settings where biofilms-related infections implicated to chronic disease and treatment failure. DOI: https://doi.org/10.54633/2333-024-057-005